Design of Multi-Stable Nucleic Acid Sequences - Abfalter, Ingrid G. (Farin, 2003)
RNA molecules that can fold into two or more predefined alternative metastable structures can be designed rationally. We outline an algorithm for this task that reduces the problem to vertex coloring the union of all prescribed outerplanar secondary structure graphs. Starting from an ear decomposition of this composite graph colorings are produced by a dynamic programming procedure. Sequences can then be optimized for particular properties by means of standard optimization heuristics.